Application of flexible bis-pyrazine–bis-amide ligands to construct various polyoxometalate-based metal–organic complexes1. Issue 70 (31st July 2015) - Wang, Xiu-Li; Liu, Dan-Na; Lin, Hong-Yan; Liu, Guo-Cheng; Han, Na; Luan, Jian; Chang, Zhi-Han
<x xml:space="preserve">Abstract</x> Five novel polyoxometalates-based metal–organic complexes constructed from different types of polyanions and flexible bis-pyrazine–bis-amide ligands with different spacer lengths have been hydrothermally synthesized and structurally characterized.